Automation of pulp wood measuring : an economical analysis - Jonsson, Johan (SLU/Dept. of Forest Products, 2009)
The pulp industry in Sweden has played an important role in the country’s economy and still does. It is an energy and raw material-consuming industry with a high degree of industrialization and automation. Much work has been done to reduce labor costs by replacing manual work with technology. In this context, it is remarkable that no precise instrument has been created to help the measurement personnel in their time-consuming work on determining the volume and value of pulpwood delivered to the mills. The delivery to and measuring of raw material at the mills plays an important role in the logistics from the forests to the industry. Measurements have to be performed accurately in order to work as a basis of payment. The way the measurement procedure works today is that one truck has to stand still blocking other trucks when its load is being measured. In the future, it might be possible to speed up this procedure and reduce the manual work with automated measurement. However, transforming an acknowledged method is no easy task, it costs money and patients. For this reason it would be of interest to see whether it would be worth making the effort and whether it would be in the interest of the industry to adopt the new technique.